In their own words : voices of Jihad : compilation and commentary - Aaron, David, 1938- (Rand Corporation monograph series., 2008)
Actual statements and writings of jihadis expressing their views on virtually every subject relevant to their cause, with introductory and contextual material that provides the background and origins of what they are saying. The stories, rationales, ideas, and arguments of jihadi terrorists and those who support them should provide greater insights into their motives and plans, as well as the nature of the threat they pose.